Salience of Greater Poland Polish Phonetic Variables - Kaźmierski, Kamil; Baranowska, Karolina (My University, 2024)
This paper investigates the salience of five phonological variables: pre-sonorant voicing, nasal stopping, nasal assimilation, the czy-trzy merger, and denasalization in Greater Poland Polish. We elicited both production (audio recordings) and perception (psycholinguistic study) data from 65 participants. On this basis, we categorize the five variables with regard to the stereotype - marker - indicator scale suggested by Labov (1972). Nasal stopping and the czy-trzy merger are the most salient and the most negatively judged, suggesting they are stereotypes; pre-sonorant voicing and nasal assimilation attract little attention, suggesting they are indicators; denasalization is associated with little agreement among the participants as to its acceptability and is avoided in formal speech, suggesting it is a marker, with the caveat that denasalization is not restricted to Greater Poland Polish.
Keywords: Salience; Quantitative Sociolinguistics; Phonetic Variation; Polish; Psycholinguistics